2013
DOI: 10.1002/aqc.2382
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns and habitat use of smalltooth sawfish, Pristis pectinata, determined using pop‐up satellite archival tags

Abstract: Research on rare and threatened species is often limited by access to sufficient individuals to acquire information needed to design appropriate conservation measures. Using a combination of data from pop‐up archival transmitting (PAT) tags across multiple institutional programmes, movements and habitat use of endangered smalltooth sawfish, Pristis pectinata were determined for animals from southern Florida and the Bahamas. All P. pectinata (n = 12) generally remained in coastal waters within the region where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 27 publications
3
55
0
3
Order By: Relevance
“…Specifically, the application of stable isotope techniques on fin tissues of 2 sympatric elasmobranch species that have well-characterized diets (Snelson et al 1984, Cliff & Dudley 1991, Collins et al 2007), in conjunction with smalltooth sawfish, a variety of consumer species, and the 18S rRNA gene analysis has provi ded evidence to support the hypothesis that smalltooth sawfish feed primarily on fishes regardless of life stage. Further, this reliance on fish prey persists even though smalltooth sawfish and bull sharks Carcharhinus leucas move from estuaries to coastal habitats during their onto geny (Simpfendorfer et al 2005, Scharer et al 2012, Carlson et al 2014, Waters et al 2014. Moreover, our results support those of previous studies that suggested smalltooth sawfish and bull sharks partition their habitat while in the Charlotte Harbor estuarine system during their early life histories (see below).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, the application of stable isotope techniques on fin tissues of 2 sympatric elasmobranch species that have well-characterized diets (Snelson et al 1984, Cliff & Dudley 1991, Collins et al 2007), in conjunction with smalltooth sawfish, a variety of consumer species, and the 18S rRNA gene analysis has provi ded evidence to support the hypothesis that smalltooth sawfish feed primarily on fishes regardless of life stage. Further, this reliance on fish prey persists even though smalltooth sawfish and bull sharks Carcharhinus leucas move from estuaries to coastal habitats during their onto geny (Simpfendorfer et al 2005, Scharer et al 2012, Carlson et al 2014, Waters et al 2014. Moreover, our results support those of previous studies that suggested smalltooth sawfish and bull sharks partition their habitat while in the Charlotte Harbor estuarine system during their early life histories (see below).…”
Section: Discussionsupporting
confidence: 88%
“…data), the region in which the largest smalltooth sawfish in this study were caught and sampled. Data from studies using pop-up archival transmitting tags on larger individuals of both species after leaving their nurseries have shown that smalltooth sawfish remain almost exclusively in shallow coastal waters (<10 m; Carlson et al 2014), and while bull sharks occasionally use similar habitats, they use deeper waters and make largescale movements (Brunn schweiler et al 2010, Carlson et al 2010. These tagging data, combined with the relatively small range of δ 13 C for smalltooth sawfish and the broader range for bull sharks in this study, suggest that these 2 species continue partitioning their habitat after leaving the nursery.…”
mentioning
confidence: 99%
“…The fifth hotspot is in the lower Peace River, in the northern portion of the estuarine system, which has a natural freshwater flow regime. Freshwater inflow into the Caloosahatchee River is regulated by water-control structures (e.g., Franklin Lock) that the South Florida Water Management District uses to manage water levels in Lake Okeechobee, the largest lake in Florida (Stoker, 1992;Chamberlain and Doering, 1998;Barnes, 2005). The anticipation of increased rainfall during the wet season (June-November) or of tropical cyclones approaching the region often prompts water managers to release freshwater from Lake Okeechobee to preclude flooding of surrounding residential and agricultural areas.…”
Section: Study Areamentioning
confidence: 99%
“…Register, 2009; NMFS 1 ; Norton et al, 2012). For example, research data and encounter reports from the public of encountering this species indicate that pregnant females enter nurseries briefly, to give birth, and that juveniles occupy the tidal portions of rivers, estuaries, and coastal bays for approximately their first 3 years (to ~2.2 m in total length) (Seitz and Poulakis, 2002;Simpfendorfer et al, 2008bSimpfendorfer et al, , 2010, and larger juveniles and adults are typically found in open-water, marine habitats (Poulakis and Seitz, 2004;Carlson et al, 2014;Waters et al, 2014). Research in the Charlotte Harbor estuarine system has led to important insights into the ecology of juvenile smalltooth sawfish: 1) nursery habitats include main-stem and non-main-stem riverine habitats, and these habitats are used differently throughout ontogeny Poulakis et al, 2013); 2) juveniles have affinities for specific abiotic conditions during their nursery residency ; and 3) responses of juveniles to freshwater inflow-related changes can be delayed (Poulakis et al, 2013).…”
mentioning
confidence: 99%
“…This is particularly the case for species that live in marine habitats where they can be difficult to locate and capture (Carlson et al, 2013). One approach to overcoming these challenges is the engagement of volunteers to collect data (Foster-Smith & Evans, 2003;Holt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%